Kemampuan Matematisasi Siswa SD dalam Menyelesaikan Soal Non Rutin - Mariana Jediut; Sabina Ndiung; Fransiska Jaiman Madu (Elementary Teacher Education Program, Majalengka University, 2023)
However, it was found that there are still many elementary school students who have not been able to change problems in the form of mathematical modeling and are less precise in applying various problem-solving strategies. This study aims to describe the mathematization ability of elementary school students in the Ponggeok cluster of Satar Mese sub-district. This type of research is quantitative with survey method. The population in this study were all grade IV elementary school students in the Ponggeok Cluster, totaling 98 people. The research sample amounted to 58 fourth grade students who attended SDN Damu, SDK Ponggeok, and SDI Lada. The sample was determined by purposive sampling technique. The data collection technique used is a test and the instrument is a test question in the form of a non-routine description. The data were analyzed based on the achievement of each indicator of students' mathematical ability. The results showed that students have not been able to achieve all indicators of mathematization ability. In this case, most students reach one of the stages of the mathematization ability process, namely converting problems into mathematical symbols. In addition, there are also students who only write the final result of the problem presented in the test question. In this case 28 students reached one of the stages of the mathematization ability process, namely converting problems into mathematical symbols. In addition, there are 30 students who only write the final result of the problem presented in the test question. Thus it can be said that the mathematical ability of grade IV elementary school students in the Ponggeok Cluster is still relatively low.